A triterpene and four sesquiterpenes from the Vietnamese sea hare Aplysia dactylomela - Pham, Thanh Binh; Duong, Thu Trang; Vu, Thanh Trung; Kieu, Thi Phuong Linh; Le, Ba Vinh; Nguyen, Phuong Thao; Nguyen, Chi Mai; Tran, My Linh; Nguyen, Van Thanh (Vietnam Journal of Marine Science and Technology, 2026)
The present study aimed to investigate the chemical constituents and biological activities of the marine mollusk Aplysia dactylomela collected from Quang Ngai Province, Vietnam. Chemical investigation of the methanolic extract of this organism led to the isolation of five compounds, including thyrsiferol (1), 11-hydroxy-8-oxo-β-cyperon (2), (+)-elatol (3), [3(15)E,4Z,6S,9S,10R]-10,15-dibromochamigra-3(15),4,7(14)-trien-9-ol (4), and pacifidiene (5). The chemical structures of these metabolites were elucidated from high-resolution electrospray ionization mass spectrometry (HR-ESI-MS) and 1D/2D NMR spectral data. Notably, this is the first report of compound 2 being isolated from the species A. dactylomela, and its complete NMR spectral assignments are provided here for the first time. All isolated metabolites were further evaluated for their in vitro cytotoxic activity against three human cancer cell lines, namely lung (A549), breast (MCF-7), and liver (HepG2) cancers. Among the tested compounds, compound 3 exhibited significant cytotoxicity against all tested cell lines, with IC50 values ranging from 5.07 ± 0.96 to 6.55 ± 0.44 μM.